Collagen network remodelling and left ventricular function in constrictive pericarditis. - Chello, M. (1996)
OBJECTIVE: To investigate whether patients with constrictive pericarditis have changes in collagen content and architecture that could influence left ventricular function. DESIGN: Cohort study. SETTING: University teaching hospital. PATIENTS: Biopsy specimens of myocardium from 13 patients admitted consecutively for treatment of chronic constrictive pericarditis were compared with normal heart tissue taken at necropsy from 15 patients free of cardiac disease. INTERVENTION: Pericardiectomy through median sternotomy. Biopsy specimens (4 or 5) were taken from the left ventricular free wall. MAIN OUTCOME MEASURES: Biochemical and histological assessment of total collagen content, relative proportion of type I and III collagen, and amount of orthogonal collagen fibre meshwork (crosshatching) in the left ventricular tissue. RESULTS: There was more collagen in the myocardium of patients with constrictive pericarditis than in controls when measured either biochemically by hydroxyproline content (89.4 v 50.4 mg/g dry weight) or by histological measurement of the collagen fraction of the myocardium (2.4% v 7.0%). Neither of these measurements, however, correlated with left ventricular ejection fraction, pulmonary wedge pressure, or right ventricular end diastolic pressure. The thickness of the fibrous trabeculae in the myocardium was, however, inversely related to both left ventricular ejection fraction (r = -0.76) and deceleration time (r = -0.68). Trabecular thickening was also related to NYHA class, with those in class III and IV having the greatest thickening. CONCLUSION: Changes in collagen content and architecture may contribute to impaired ventricular function in patients with chronic constrictive pericarditis.